Dispersal dilemmas - Siqueira, Tadeu [UNESP]; Wunderlich, Alison [UNESP] (Springer Nature, 2018)
A coordinated distributed experiment, replicated across multiple labs and multiple taxa, reveals that both resources and predators govern dispersal between habitats, affecting local and regional stability of biological communities.